PENGARUH GAME ELEMENTS TERHADAP CUSTOMER ENGAGEMENT DAN PERCEIVED PLAYFULLNESS DAN DAMPAKNYA TERHADAP BEHAVIORAL INTENTION PADA PENGGUNA APPLIKASI KOPI KENANGAN DI JABODETABEK - Dharmawan Freddy Kosasih; Margaretha Pink Berlianto (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
This study aims to examine the effect of game elements on customer engagement, perceived playfulness, Attitude, & Behavioral Intention among users of the Kopi Kenangan App in the Greater Jakarta area. This study uses a quantitative, cross-sectional method. The sampling technique is non-probability sampling, specifically purposive sampling. Data were collected through an electronic 5-point Likert-scale questionnaire administered to 250 respondents aged 18–45 years residing in Jabodetabek who have used the Kopi Kenangan App. Data analysis was performed using PLS-SEM with SmartPLS 4.0.9.9. The results show that game elements have a significant positive effect on customer engagement and perceived playfulness. These two variables also have a significant positive effect on improving user Attitude, which ultimately increases Behavioral Intention. F&B app managers are advised to optimize gamification design to increase user enjoyment and engagement, thereby encouraging sustainable usage intentions.